Penerapan Metode Simple Additive Weighting (SAW) Dalam Pemilihan Karyawan Berprestasi Berbasis Web - Taufik Kurnialensya; Yuli Fitrianto (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
Company XYZ in twelve months always has a program for selecting outstanding employees. . This selection process requires accuracy and time, because employee data will be compared with the criteria set by company XYZ. The criteria set by XYZ company are work discipline, employee attendance, obedience, teamwork, work period, work spirit, and work loyalty. The selection of outstanding employees is not right on target, because it is not based on weighting. In accordance with the regulations set by the XYZ company in the selection of outstanding employees, criteria are needed to determine who will be selected to receive the outstanding employee award.The simple additive weighting (SAW) method is often also known as the weighted addition method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method requires the process of normalizing the decision matrix (X) to a scale that can be compared with all existing alternative ratings. By using the SAW method can solve problems in the selection of outstanding employees.